2022
DOI: 10.3390/jof8030231
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Fusarium solani Species Complex Isolates from the Ambrosia Beetle Xylosandrus morigerus

Abstract: Ambrosia beetles are insect vectors of important plant diseases and have been considered as a threat to forest ecosystems, agriculture, and the timber industry. Several factors have been suggested as promoters of the pathogenic behavior of ambrosia beetles; one of them is the nature of the fungal mutualist and its ability to establish an infectious process. In Mexico, Xylosandrus morigerus is an invasive ambrosia beetle that damages many agroecosystems. Herein, two different isolates from the X. morigerus ambr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The combined tef-1 and rpb2 sequence data set was used for phylogenetic analysis of the F. solani species complex, following the identification techniques employed in earlier studies [ 50 , 55 ]. This phylogenetic analysis included 41 taxa and the aligned data set contained 1415 bp including gaps ( tef-1 : 1–603 and rpb2 : 604–1415).…”
Section: Resultsmentioning
confidence: 99%
“…The combined tef-1 and rpb2 sequence data set was used for phylogenetic analysis of the F. solani species complex, following the identification techniques employed in earlier studies [ 50 , 55 ]. This phylogenetic analysis included 41 taxa and the aligned data set contained 1415 bp including gaps ( tef-1 : 1–603 and rpb2 : 604–1415).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluated the antagonistic activity of bacteria strains isolated from P. schiedeana and P. mexicana against phytopathogenic fungus Fusarium sp., we evaluated the inhibitory radial growth of Fusarium sp. strain INECOL_BM-06 a phytopathogenic fungus [34]. We found that the strains PsH3-014(14D) and Hay2-01H(7) caused a signi cant growth inhibition to Fusarium sp.…”
Section: Bacterial Strains Characteristics and Molecular Identi Cationmentioning
confidence: 83%
“…To determine if the bacterial strains had an antagonistic effect against the growth of Fusarium sp. pathogenic strain INECOL_BM-06 provided by the Phytopathology Laboratory at Institute of Ecology, A.C. (INECOL) [34]; both organisms were co-cultured in Petri plates of Potato Dextrose Agar (PDA) media, three petri plates, per bacterial strain plus three petri plates only with Fusarium sp. as absolute growth control, which we consider "negative control".…”
Section: Biomass and Anthocyanin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the less frequent transmission routes include insects acting as vectors for plant pathogens. Recent study have proven that beetles from the species Xylosandrus morigerus can be effective vectors for the Fusarium solani species complex (FSSC), even though the two isolates showed a considerable level of diversity and were reported to be pathogenic to different plant species [ 6 ].…”
mentioning
confidence: 99%